Evaluation of Property Productivity in Creative Space Development: A Case Study of The Hallway Space in Kosambi Market, Bandung - Fauzan Baldomero Mahyudin; Farah Saniya Zahra; Allis Nurdini (International Journal Labs, 2025)
Urbanization and creative lifestyles have driven the emergence of new collaborative spaces in urban areas, including creative spaces built atop traditional markets. This study evaluates the property productivity of The Hallway Space, a youth-culture-based creative space developed on the upper floor of Pasar Kosambi, Bandung, using the Property Productivity Analysis framework (Wilkinson & Reed, 2008), which includes physical, legal, and locational attributes. The research adopts a qualitative-descriptive approach through a case study strategy, utilizing data triangulation from primary sources (semi-structured interviews with the manager and tenants) and secondary sources (Google Maps online reviews analyzed through content analysis, text mining, and open coding). The findings indicate that The Hallway Space successfully creates social and visual added value, enhances place identity, and fosters community interaction, though it still faces challenges related to thermal comfort, navigation, and vertical accessibility. Most visitors perceive the space positively in terms of activities and social atmosphere, despite issues concerning signage and ventilation. This study highlights the importance of evaluating creative spaces not only from social and cultural aspects but also as productive and sustainable commercial properties, particularly in the context of adaptive reuse within traditional market environments.